APPLICATION OF HAAR-WAVELET METHOD TO LAYERED STRUCTURES - Pysarenko , Oleksandr (Collection of scientific papers «ΛΌГOΣ», 2025)
High-performance composites exhibit a number of exceptional mechanical, thermal and electrical properties. Structural applications of laminated composites can be used in various industrial fields that require a material with high strength, stiffness and low weight [1]. It is worth noting a number of experimental and analytical studies of the mechanical properties of such laminated structures. It was found that the strength, stiffness, high Young’s modulus and tensile strength of reinforced composites can be significantly improved by minor additives that modify their laminated structure. The non-uniform distribution of the reinforcement phase allows to classify reinforced composites with a modified layered structure as functionally graded materials [2]. Numerous studies of the mechanical properties of functionally graded composites in the form of beams, plates and shells were primarily focused on the analysis of their behavior under static bending, elastic loss of stability, as well as linear and nonlinear characteristics of free vibration.